Automatic controller for running single phase generator using pc / Nik Hamidi Nik Hamid - Nik Hamid, Nik Hamidi (1994)
The objectives of this project is to develop an automatic system for running of single phase generator to provide backup power supply to UPS using PC (personal computer) when the main power supply failure. This project is concerned with the computer as a controller operating through a low cost special interface to control the relays switching. The interface uses the standard RS-232-C serial communication port which means it can interface between computer and control devices. The software is designed to monitor the existing and detects failure in supply system and to control the output devices. The simple QBASIC program is developed to manipulate the system.